-3-y-X=0

Simple and best practice solution for -3-y-X=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3-y-X=0 equation:


Simplifying
-3 + -1y + -1X = 0

Reorder the terms:
-3 + -1X + -1y = 0

Solving
-3 + -1X + -1y = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + -1X + 3 + -1y = 0 + 3

Reorder the terms:
-3 + 3 + -1X + -1y = 0 + 3

Combine like terms: -3 + 3 = 0
0 + -1X + -1y = 0 + 3
-1X + -1y = 0 + 3

Combine like terms: 0 + 3 = 3
-1X + -1y = 3

Add 'y' to each side of the equation.
-1X + -1y + y = 3 + y

Combine like terms: -1y + y = 0
-1X + 0 = 3 + y
-1X = 3 + y

Divide each side by '-1'.
X = -3 + -1y

Simplifying
X = -3 + -1y

See similar equations:

| 2x-8=-8x-24 | | 2(4-9w)= | | 57+51+9x=180 | | 6(-2y-16)-2y=-12 | | 6p+b=144 | | -18s+10=-17s | | (X+18)=(x+10) | | 18x-12=17x-2 | | 0=-x+5y | | 3(2z)=-3 | | -690=10(-7x+22) | | 5x-9x+3=17 | | 8x-4(-3+2)=-12 | | 2m+6n-9(5m-4n)= | | (2x-8)(2x-8)=44 | | 12x+15y=90 | | 100-66=31y-35y | | 10=-x+2y | | 2x-18=9x+6 | | 7.57x+22.71=45.42 | | 5+3t-3=8t+14-3t | | (X+14)=(x-20) | | 25=2(x+3) | | 2x+2(x-28)=-104 | | 2x-1-x=9x-3 | | -18+10=-17s | | (x+4)(x-4)=4 | | 5+y=0.0024x | | 3x+2(x-28)=-104 | | y=3x^2-6x+200 | | 2x-8(2x-8)=44 | | 25u+75=23u+92 |

Equations solver categories